Neutron-Induced Radiation Effects in UMOS Transistor - Alberton, S G; Bôas, A C V; Medina, N H; Guazzelli, M A; Aguiar, V A P; Added, N; Federico, C A; Gonçalez, O L; Cavalcante, T C; Pereira Junior, E C F; Vaz, R G (Journal of physics. Conference series, 2022)
Ground level electronics and avionics systems may suffer from radiation effects induced by neutrons. Neutrons can induce radiation effects in electronic devices via fusion-evaporation nuclear reactions, but few studies have been reported for technologies such as UMOSFET. In this work, estimates and experimental studies on neutron-induced radiation effects via nuclear reactions in a Si-based UMOSFET are presented. Methods for probability estimates of neutron-induced Single-Event Effects (SEEs) in Si-based power transistors and neutron beam energy measurement is presented. The energy spectrum of a UMOSFET subject to fast neutron irradiation was then compared to that of a high charge collection efficiency silicon particle detector.